Knowledge, perception and practices of oil palm smallholders toward ganoderma basal stem rot disease in Sabah - Assis Kamu; Bonaventure Boniface; Abdul Rahim Awang,; Affendy Hassan,; Mohammad Amizi Ayob,; Siti Kalsom Yulo (2014)
Oil palm or scientifically known as Elaeis guineensis Jacq. is the most important commodity crop as compared to other crops in Malaysia. Currently, Malaysia’s oil palm industry is facing two main problems, namely lack of manpower resources and incurable oil palm disease. As far as the disease problem to oil palm in Malaysia is concerned, Ganoderma basal stem rot (BSR) remains an important disease. Oil palm smallholders play very important to the oil palm industry. Unfortunately, many the farmers did not realize that their fields were infected with BSR and failed to recognize the extent of disease incidence. Therefore, this study was conducted to identify the knowledge, attitude, and practices of oil palm smallholders toward the disease especially in Sabah. A cluster analysis on the knowledge of the respondents towards BSR disease showed that there were two categories of respondents, and the level of their knowledge is significantly associated with their category of smallholders either independent or organized smallholders. Based on the factor analysis, there were two main problems or issues faced by the respondent in dealing with the disease, namely lack of knowledge about the disease and lack of money, labour and time to overcome the disease. In terms of practices, most of the respondents did not conduct any census on the disease, did nothing to the infected palms, and did nothing to prevent their field from being infected. As conclusion, the knowledge of oil palm smallholders towards BSR disease is still low. The relevant parties should focus on how to improve the knowledge as well as the awareness of oil palm smallholders on this devastating disease.